Outpatient Foley Catheter for Induction of Labor in Obese Nulliparous Patients: A Secondary Analysis of OFFSITE II Randomized Controlled Trial - Seasely, Angela R.; Xue, Yumo; Ausbeck, Elizabeth B.; Jauk, Victoria C.; Blanchard, Christina T.; Files, Pamela; Kuper, Spencer C.; Casey, Brian M.; Szychowski, Jeff M.; Harper, Lorie M.; Tita, Alan T.; Subramaniam, Akila (American Journal of Perinatology, 2022)
Objective In the OFFSITE II randomized controlled trial, outpatient cervical ripening with a Foley catheter (CF) in nulliparous patients undergoing elective induction of labor (eIOL) shortened the time from admission to delivery. Given that patients with obesity have protracted labor and higher rates of failed IOL, we sought to determine if outpatient ripening with a CF may be even more beneficial for this high-risk group.Study Design We performed a secondary analysis of the OFFSITE II randomized controlled trial. For this analysis, all patients from the primary trial were classified by their intervention assignment (inpatient vs. outpatient) and also by their admission body mass index (BMI) class (BMI ≥ 30 and BMI < 30 kg/m2). The primary outcome was time from labor and delivery (L&D) admission to delivery. Secondary outcomes included cesarean delivery, time from admission to hospital discharge, and rates of clinically diagnosed chorioamnionitis and endometritis.Results In patients with BMI ≥ 30, the primary outcome, time from admission to delivery, (18.0 [13.5–20.9] vs. 20.4 [16.6–31.3] hours, p = 0.01), as well as total hospitalization length (3.2 [2.5–3.3] vs. 3.4 [3.1–4.3] days, p = 0.02) were shorter in the outpatient group. There were no differences in rates of chorioamnionitis or endometritis in outpatient compared with inpatient CF. Furthermore, in those with a BMI ≥ 30, the cesarean rate was significantly lower with outpatient CF (19.4% vs. 44.7%, p = 0.03); it was not statistically different in patients with BMI < 30.Conclusion In this exploratory retrospective secondary analysis of the OFFSITE II randomized control trial, we found that in patients with BMI ≥ 30 undergoing eIOL, outpatient CF was associated with a lower time from L&D admission until delivery. This was also associated with a shorter time of total hospital duration and decreased the rate of cesarean, a benefit not detected in the overall analysis presented in the primary study. In nulliparas undergoing induction of labor, ripening with outpatient cervical Foley may even more significantly reduce labor duration, total hospital duration, and the rate of cesarean in patients with obesity.Key Points
Keywords: induction of labor; cervical ripening; obesity; outpatient Foley catheter